Recent Advances in Synthesis and Biological Assessment of Quinoline‐Oxygen Heterocycle Hybrids. Issue 20 (26th May 2021) - Kumar, Gourav; Saroha, Bhavna; Kumar, Ramesh; Kumari, Meena; Kumar, Suresh
Abstract: The exploration of hybrid molecules for targeting various diseases represents a highly promising approach which has showcased significant momentum worldwide, in the last two decades. Diversely substituted quinoline scaffolds present in naturally occurring bioactive compounds, signify their role in various biological processes and stimulated the research developments around it, for diverse therapeutic applications. With the ongoing search for suitable pharmacophores, the quinoline derivatives have emerged as versatile compounds possessing significant and broad spectrum of biological activities. Further, conjugation of quinoline with other bioactive heterocycles containing oxygen yielded hybrid organic frameworks with improved therapeutic profile leading to an emerging paradigm and tremendous growth in the contemporary drug discovery regime. The synthesis of these hybrid skeletons with high efficiency still remains the most strenuous task and a lot of research work is being performed in this direction. In the present article, we have reviewed the synthetic protocols leading to quinoline‐oxygen heterocycle hybrids and also highlighted the systematic and biological assessment of developed pharmacophores. Abstract : Hybrid molecules of quinoline and oxygen based heterocycles, of natural and synthetic origin are the center of interest both for chemists and pharmacologists and have paved a suitable platform for drug development. In the present article, we have systematically reviewed the synthesis and biological assessment of quinoline‐oxygen heterocycle hybrids and outlined predominant contributions.